Metafizika bede (Attila József, A. B. Šimić, Srečko Kosovel) - Lukács, István (Slavia Centralis, 2020)
Metaphysic of Misery (Attila József, A. B. Šimić, Srečko Kosovel) Expressionism was the most influential artistic movement among the Central-European Avantgarde. It developed at almost the same time as it did in Hungarian, Croatian, and Slovenian literature and was based on "hybrid-poetical construction" with German inspiration. This fact in itself might have formed a reason for analysis of the region’s literatures; however, this has not yet been completed.